Protein-encapsulated in mesoporous silica nanoparticles for the the treatment of bacterial biofilms - Gouda, Mariam (My University, 2019)
80% of infections are estimated to be biofilm related, which are extremely resistant to anti-microbials. It remains an unmet need to develop medications to treat biofilms. Currently, there are evolving approaches that use protein drugs, such as antimicrobial peptides against biofilms, yet they are biologically unstable. In this project, the aim was to develop a nanosystem that efficiently protects and delivers a model protein drug, lysozyme, throughout biofilm matrices. This was realized using large-pore mesoporous silica nanoparticles as nanocarriers, coated with a pH responsive polymer. Methods: Particles were synthesized via an interfacial synthesis method. Lysozyme was loaded into the particles through the immersion method. Protein release was studied under both neutral and acidic conditions (biofilm nature). Loaded particles were coated by the aid of a 3D co-flow microfluidic glass capillary device. Results: Mesoporous nanoparticles were uniform in shape and size with a polydispersity index of ~0.08. Lysozyme was loaded with a high loading capacity of 446.5 mg/g. The release trend showed a burst release of the drug at acidic pH, while a sustained release in neutral conditions. Acetalated dextran (Ac-Dex), a pH responsive polymer, couldn’t be used solely as a coat. It dissolves in ethanol, which may lead to protein denaturation. Hence, another polymer, that dissolves in water, was used as the inner coat, and Ac-Dex acted as the outer coat. The innermost polymer coating was optimum at a concentration ratio of 1:5 and a flow rate ratio of 2:40 ml/hr. However, acetalated dextran coating was unsuccessful in all attempts. Conclusion: The nanosystem is successful in accommodating and releasing a protein drug. However, there is a need to further investigate other types of coating polymers.
Keywords: Biofilm, Mesoporous particles, Microfluidics, Nanoprecipitation